Daya saing dan faktor-faktor yang mempengaruhi ekspor kopi Arabika Indonesia di pasar internasional - Viza Muttoharoh; Rahma Nurjanah; Candra Mustika (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2018)
This study aims to analyze: 1) the competitiveness of Indonesian Arabica coffee in the international market; 2) the effect of coffee production, economic growth and exchange rates on Arabica coffee exports. The data used are time series data for the period of 2000 - 2016. The competitiveness of Indonesian Arabica coffee is analyzed by Revealed Comparative Advantage (RCA). To analyze the effect of coffee production, economic growth and exchange rates on Arabica coffee exports OLS multiple regression models were used. The results of the study found that: 1) during the period 2000-2016 Arabica Indonesia's coffee power had strong competitiveness because the RCA index value was greater than one; 2) coffee production and exchange rates have a significant effect while economic growth has no significant effect on the export of Indonesian Arabica coffee